Low serum albumin level deteriorates prognosis in azacitidine-treated myelodysplastic syndromes patients – results of the PALG study 'PolAZA'. Issue 1 (1st January 2021) - Mądry, Krzysztof; Lis, Karol; Tukiendorf, Andrzej; Szwedyk, Paweł; Kapelko-Słowik, Katarzyna; Subocz, Edyta; Gołos, Aleksandra; Makowska, Wioletta; Masternak, Anna; Kopińska, Anna; Czemerska, Magdalena; Zawadzka-Leska, Sara; et al.
ABSTRACT: Background: Azacitidine (AZA) is the standard of care for higher-risk myelodysplastic syndrome (HR-MDS) patients ineligible for intensive therapy. Clinical outcome discrepancies reported in clinical trials and real-life settings stimulate the search for new prognostic factors. Methods: We retrospectively evaluated 315 MDS, 20–30% blast acute myeloid leukemia (AML) and chronic myelomonocytic leukemia (CMML) patients treated with azacitidine in 12 centers cooperating within the Polish Adult Leukemia Group (PALG). Results: The median number of AZA cycles was 7 (1–69) and 24% patients received fewer than 4 cycles (early failure, EF). Serum albumin level was an independent predictor of EF occurrence. Complete remission (CR) was obtained in 20% and partial remission (PR) in 12% of patients. Hematologic improvement – erythroid (HI-E), neutrophil (HI-N), or platelet (HI-P) was achieved in 51%, 36%, and 48% of patients, respectively. No factors significantly predicted CR or PR in the multivariate analysis. For HI-E and HI-P, lower LDH level predicted response. Median survival was 15 (13–19) months. Lower serum albumin level, serious infection and receiving <4 AZA cycles independently predicted a worse overall survival (OS) ( p < 0.05). Conclusion: Serum albumin assessment before azacitidine treatment can help to identify patients with higher risk of early failure and worse clinical outcome.